Challenges in the application of a WRF/Urban-TRNSYS model chain for estimating the cooling demand of buildings: A case study in Bolzano (Italy). (28th May 2018) - Pappaccogli, Gianluca; Giovannini, Lorenzo; Cappelletti, Francesca; Zardi, Dino
Abstract : In the present study, a WRF/Urban-TRNSYS model chain is proposed to evaluate the cooling demand of buildings located in an urban area. A case study is proposed to show the applicability of the method for a hypothetical residential building located in the city of Bolzano (Italy) on a clear-sky hot day in summer. WRF/Urban results were first validated against measurements from permanent weather stations located both in the urban area and in the surrounding countryside. Then, several TRNSYS simulations were performed, in order to assess the impact of the gridded input from WRF/Urban against both measurements from a weather station located close to the sample building and to standard data from the Test Reference Year (TRY). Compared with estimates using input data from the weather station, the daily cooling demand of the sample building estimated by WRF/Urban-TRNSYS differed by only 6% to 8%, while differences of 60% were found when using standard TRY data. Moreover, results show that energy estimates obtained by means of WRF/Urban-TRNSYS model chain satisfy the standard requirement suggested by Ashrae Guidelines 14–2002, suggesting that this model chain is a useful tool for the estimation of real buildings energy consumption.